New Variant of Vibrio parahaemolyticus , Sequence Type 3, Serotype O10:K4, China, 2020 - Huang, Yan; Du, Yue; Wang, Hong; Tan, Dongmei; Su, Airong; Li, Xiugui; Kan, Biao; Lan, Lan; Qu, Cong; Pang, Bo; Shi, Yunliang; Lin, Mei (Emerging infectious diseases, 2022)
In 2020, a new serotype of Vibrio parahaemolyticus O10:K4 emerged and caused several outbreaks and sporadic cases in Guangxi, China. Phylogenetic analysis indicated that those strains are new variants of the sequence type 3 pandemic clone. The new serotype may become dominant, warranting enhanced investigations and surveillance.